2002
DOI: 10.1590/s0100-204x2002000800007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of aluminum tolerance in Brazilian barleys

Abstract: -Aluminum (Al) toxicity is a major factor limiting barley growth in acid soils, and genotypes with adequate level of tolerance are needed for improving barley adaptation in Brazil. To study the inheritance of Al tolerance in Brazilian barleys, cultivars Antarctica 1, BR 1 and FM 404 were crossed to sensitive Kearney and PFC 8026, and intercrossed. Parental, F 1 , F 2 and F 6 generations were grown in nutrient solution containing 0.03, 0.05 and 0.07 mM of Al and classified for tolerance by the root tip hematoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The present results are in agreement with the previous results on other crops (Rhue et al. 1978, Somers and Gustafson 1995, Riede and Anderson 1996, Minella and Sorrells 2002, Raman et al. 2002, Wang et al.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The present results are in agreement with the previous results on other crops (Rhue et al. 1978, Somers and Gustafson 1995, Riede and Anderson 1996, Minella and Sorrells 2002, Raman et al. 2002, Wang et al.…”
Section: Discussionsupporting
confidence: 94%
“…Several studies have demonstrated that inheritance of Al tolerance is simple (Rhue et al. 1978, Minella and Sorrells 2002, Singh and Choudhary 2010) and complex (Lafever and Campbell 1978, Aniol and Gustafson 1984, Aniol 1990, Araujo et al. 1992, Carver and Ownby 1995).…”
mentioning
confidence: 99%
“…Several studies have demonstrated that Al tolerance is a simple (Rhue et al. , Minella and Sorrells , Singh and Choudhary ) or a complex as well (Lafever and Campbell , Aniol and Gustafson , Aniol ) trait. Information on the accumulation of aluminium and callose and inheritance pattern of Al 3+ tolerance in lentil is not available.…”
mentioning
confidence: 99%
“…2006, Singh et al. 2007b) were chosen because such techniques have given consistent results and are routinely used in genetic studies (Anas and Yoshida 2000, Minella and Sorrells 2002).…”
mentioning
confidence: 99%